Robust H∞ control of an uncertain bilateral teleoperation system using dilated LMIs - Gormus, Bilal; Yazici, Hakan; Kucukdemiral, Ibrahim Beklan (SAGE PUBLICATIONS LTD, 2022)
A robust state-feedback H-infinity controller is proposed for an uncertain bilateral teleoperation system having norm-bounded parametric uncertainties on mass and damping coefficients of the considered master/slave system. The proposed method ensures robust stability and successful reference tracking and force reflection performance. While Lyapunov stability is used to ensures asymptotic stability, the H-infinity norm from exogenous input to the controlled output is utilized in satisfying the reference tracking and force reflection. As two performance objectives and robust stability requirement are conflicting with each other, the proposed controller reduces the associated conservatism with dilated linear matrix inequalities. Standard and dilated linear matrix inequality-based robust H-infinity state-feedback controllers are performed with a one degree of freedom uncertain master/slave system under reference signal and environmental-induced exogenous force. Numerical simulation results show that the dilated linear matrix inequality-based H-infinity control satisfies lower H-infinity norm than a standard H-infinity control. Moreover, the proposed controller demonstrates a very successful performance in achieving performance objectives despite the stringent norm-bounded parameter uncertainties.
Keywords: Dilated linear matrix inequalities; robust H infinity controller; norm-bounded uncertainties; bilateral teleoperation system; TIME-DELAY; STABILITY; DESIGN; Automation & Control Systems; Instruments & Instrumentation